Improvements in body mass index of children with cystic fibrosis following implementation of a standardized nutritional algorithm: A quality improvement project - GÖKDEMİR, YASEMİN; ERDEM ERALP, ELA; ERGENEKON, ALMALA PINAR; YILMAZ YEĞİT, CANSU; KARADAĞ, BÜLENT TANER (My University, 2023)
BackgroundA collaboration between the University of Michigan (UM) Cystic Fibrosis Center (CFC) and Marmara University (MU) CFC was initiated in MU through conducting Quality Improvement projects (QIP). The global aim was to improve nutritional status of children with CF (cwCF), with a specific aim to increase the mean BMI percentile (BMIp) for cwCF by 10 percentile points in 12 months. MethodsBody mass index (BMI) percentiles of cwCF were categorized as: nutritionally adequate (BMIp >= 50%); at risk (BMIp 25%-49%); urgently at risk (BMIp 10%-25%); critically at risk (BMIp < 10%). Appropriate interventions were made according to BMIp category every three months. Forced expiratory volume in one-second percent predicted (FEV1pp), and health-related quality of life (HRQoL) were evaluated. ResultsOne hundred and eight-two cwCF with a mean age of 9.1 +/- 4.3 years were included in the project. Baseline BMIp increased from 25.6 to 37.2 at the 12th month (p < 0.001). In the critically at-risk group BMIp increased from 3.6 to 20.5 (p < 0.001), in the urgently at risk group from 15.9 to 30.8 (p < 0.001), in the at risk group from 37.0 to 44.2 (p < 0.079) and in the nutritionally adequate group the increase was from 66.8 to 69.5 (p < 0.301). FEV1pp also improved significantly, from 81.3 +/- 20.6 to 85.9 +/- 20.8 (p < 0.001). Physical functioning, eating problems, and respiratory symptoms domains of the HRQoL evaluation improved (p < 0.05). ConclusionThis project has led to significant improvements in BMIp, FEV1pp and HRQoL of cwCF; similar projects could easily be implemented by centers in other developing countries.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); SOLUNUM SİSTEMİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); RESPIRATORY SYSTEM; Solunum Bakımı; Pediatri; Akciğer ve Solunum Tıbbı; Pediatri, Perinatoloji ve Çocuk Sağlığı; Respiratory Care; Pediatrics; Pulmonary and Respiratory Medicine; Pediatrics, Perinatology and Child Health; body mass index; children; cystic fibrosis; nutrition; OF-LIFE; MEDICAL-PRACTICE; HEALTH-CARE; PATTERNS; OUTCOMES; body mass index; children; cystic fibrosis; nutrition